Genetic diversity analysis in guava (Psidium guajava) on the basis of morphological and physico-chemical traits - SINGH, D; GILL, M I S; BOORA, R S; ARORA, N K (The Indian Journal of Agricultural Sciences, 2015)
Assessment of genetic diversity in the available germplasm is the prerequisite for development of improved genotypes through planned breeding programmes. In view of this, thirty five guava (Psidium guajava L.) genotypes maintained at the Fruit Research Farm of Punjab Agricultural University, Ludhiana and its Regional Fruit Research Station, Bahadurgarh, Patiala were evaluated for tree, vegetative, reproductive, fruit and seed characters based on UPOV descriptors during years 2010 to 2013. Morpho physiological data was subjected to Mahalanobis D2 statistic and it grouped the tested genotypes into six clusters with Cluster III and V showing maximum inter cluster distance. Cluster I, cluster IV, cluster V and cluster VI showed intra cluster distance of 55.12, 55.40, 50.70 and 61.84, respectively, indicating that the genotypes in these clusters have dissimilarity for morphological features and performance. Cluster III had highest mean value for fruit weight (312.39 g), fruit length (109.60 mm), fruit width (72.88 mm) and fruit outer flesh thickness (17.95 mm) and least mean values for seed weight per 100 g of fruit (0.933 g). Cluster V was characterized by minimum mean value for 100-seed weight (1.017 g) and maximum value for total soluble solids (11.60 %) and titrable acidity (0.486 %). Contribution towards observed diversity was found to be 47.90, 16.73, 13.11 and 10.76 per cent for seed weight per fruit, fruit diameter, 100-seed weight and leaf width. Genotypes from Cluster III, V and IV may be chosen for intercrossing to get the desired trait combinations through high heterotic response and superior recombinants in their progenies.